PPARA intron polymorphism associated with power performance in 30-s anaerobic Wingate Test - Petr, Miroslav; Stastny, Petr; Št'astný, Petr; Pecha, Ondřej; Šteffl, Michal; Šeda, Ondřej; Kohlíková, Eva (PLoS One, 2014)
To date, polymorphisms in several genes have been associated with a strength/power performance including alpha 3 actinin, ciliary neurotrophic factor, vitamin D receptor, or angiotensin I converting enzyme, underlining the importance of genetic component of the multifactorial strength/power-related phenotypes. The single nucleotide variation in peroxisome proliferator-activated receptor alpha gene (PPARA) intron 7 G/C (rs4253778; g.46630634G>C) has been repeatedly found to play a significant role in response to different types of physical activity. We investigated the effect of PPARA intron 7 G/C polymorphism specifically on anaerobic power output in a group of 77 elite male Czech ice hockey players (18-36 y). We determined the relative peak power per body weight (Pmax.kg(-1)) and relative peak power per fat free mass (W.kg(-1)FFM) during the 30-second Wingate Test (WT30) on bicycle ergometer (Monark 894E Peak bike, MONARK, Sweden). All WT30s were performed during the hockey season. Overall genotype frequencies were 50.6% GG homozygotes, 40.3% CG heterozygotes, and 9.1% CC homozygotes. We found statistically significant differences in Pmax.kg(-1) and marginally significant differences in Pmax.kg(-1)FFM values in WT30 between carriers and non-carriers for C allele (14.6 ± 0.2 vs. 13.9 ± 0.3 W.kg(-1) and 15.8 ± 0.2 vs. 15.2 ± 0.3 W.kg(-1)FFM, P = 0.036 and 0.12, respectively). Furthermore, Pmax.kg(-1)FFM strongly positively correlated with the body weight only in individuals with GG genotypes (R = 0.55; p<0.001). Our results indicate that PPARA 7C carriers exhibited higher speed strength measures in WT30. We hypothesize that C allele carriers within the cohort of trained individuals may possess a metabolic advantage towards anaerobic metabolism.
Keywords: Young Adult; Gene Frequency; Male; Genotype; mladý dospělý; Adolescent; Adult; anaerobióza; dospělí; PPAR alfa; mužské pohlaví; jednonukleotidový polymorfismus; PPAR alpha; Body Weight; mladiství; zátěžový test; Introns; frekvence genu; Exercise Test; introny; Polymorphism, Single Nucleotide; lidé; sportovní výkon; Humans; Anaerobiosis; genotyp; Athletic Performance; tělesná hmotnost